Tierra como materia prima sostenible y alternativa frente a la desertificación: Prototipo de Vivienda Rural, Colectiva, Progresiva y Productiva para el Desierto de la Tatacoa (Villavieja, Huila) (2022)
Desertification is a serious problem for the Department of Huila, where 15 of 37 municipalities reveal desertified soils, a process understood as ecological degradation in which the soil progressively loses its fertility and productivity. This serio us problem is identified in the Municipality of Villavieja, this being the focal point of a rapid growth of soil erosion in the Department of Huila. Negatively affecting rural communities and their quality of life identified in a high housing deficit. Base d on this affected problem, an area of study is determined on the village of Cuzco in the Tatacoa Desert and its rural inhabitants, in search of pertinent information on environmental, housing, quality of life and productive systems that are carried out. out in the sector.